IMPLEMENTASI PENGOLAHAN KOTORAN SAPI BERBASIS SIMANTRI (SISTEM PERTANIAN TERINTEGRASI) SEBAGAI PUPUK ORGANIK PADAT DESA TIYINGGADING - Gunawan, I.G. N.W (Buletin Udayana Mengabdi; Vol 21 No 1 (2022): Buletin Udayana MengabdiDO - 10.24843/BUM.2022.v21.i01.p12, 2022)
Tiyinggading Village, Tabanan Regency, Bali Province is a village with views of hills, rice fields and mountains. This causes the existence of a tourist attraction in Tiyinggading Village. Some of the people of Tiyinggading Village work as farmers and raise cows to cultivate their agricultural land. One of them is implementing livestock in the village with the KTT Manik Amertha. However, the field conditions for the cattle of the KTT Manik Amertha, Tiyinggading Village, still do not meet the standards. The condition of the appropriate machines in the livestock land is still not maintained and many are damaged. In addition, the members of the Manik Amertha Summit do not have the technical understanding and expertise so that cow dung accumulates because it is not processed and the solid organic fertilizer produced does not meet the standards. The problem is getting worse because of the lack of sales partners related to solid organic fertilizer products processed by these partners. With the implementation of this community empowerment program, the partners experienced improvements in the process of processing cow dung waste into solid organic fertilizer, increasing technical expertise in processing solid organic fertilizers and increasing the selling value of solid organic fertilizers.   Keywords: Agriculture, machine, cow dung, organic fertilizer, community empowerment